Effect of Waste Filler Materials and Recycled Waste Aggregates on the Production of Geopolymer Composites - Tammam, Yosra; Uysal, Mucteba; Canpolat, Orhan; Kuranli, Omer Faruk (SPRINGER HEIDELBERG, 2023)
In this research, the performance of fly ash/GGBS geopolymer mortars made with different quarry waste powder as filler materials by substituting the fine recycled aggregate (RS) with different ratios. Also, it was evaluated based on mechanical, physical, freeze-thaw, and microstructural analysis. Limestone waste (L), marble waste (M), and basalt waste powder (B) were used as filler materials developing eco-friendly and economical geopolymer from industrial waste as a promising sustainable area of research. Strength properties, ultrasonic pulse velocity, physical properties, freeze-thaw, XRD, and SEM analysis of geopolymer samples were investigated. The results revealed that using waste filler materials together with recycled aggregate effectively improves the mechanical properties of geopolymer composites substituting three different filling materials affected water absorption positively, strength properties, and freeze-thaw results. Current findings point to a potential solution. Successful use of fly ash, slag, recycled aggregate, and quarry waste has been achieved. The output of the study is expected to result in effective and environmentally friendly management of recycled wastes.
Keywords: Geopolymer; Fly ash; Ground granulated blast furnace; Freezing-thawing; Recycled aggregate; Waste filler materials; STRUCTURAL CONCRETE; LIMESTONE POWDER; SILICA FUME; CEMENT; MARBLE; PERFORMANCE; DURABILITY; STRENGTH; Science & Technology - Other Topics